Study on the evolution of the spatial patterns and driving factors of national agricultural cultural heritage in China - Lifei Xu; Yuyu Liao; Jun Liu (PLoS ONE, 2025)
The study analyzed the spatial distribution characteristics, evolution rules, and driving factors of 138 China’s national agricultural cultural heritage sites from 2013 to 2021 at the overall and regional levels, using kernel density analysis, Centres for standard deviation ellipse analyses, spatial autocorrelation analysis, and geographical detector analysis.The results showed that: ①From an overall perspective, the spatial pattern of China’s national agricultural cultural heritage changed greatly from 2013 to 2021, with a highly uneven spatial distribution, gradually showing a distribution pattern of "widely distributed, locally concentrated". The spatial distribution of China’s national agricultural cultural heritage is increasingly evident, and the spatial distribution type has evolved from discrete to clustered. The spatial distribution center of gravity shows a shift trajectory of "north-east, then south-east". During the study period, the X axis of the standard deviation ellipse was always greater than the Y axis, but the difference between the X and Y axes was small, indicating that the spatial distribution direction was northeast-southwest, but the directionality was weak. The types of national agricultural cultural heritage are diverse and rich, involving farmland landscapes, composite systems, crop varieties, vegetables and melons, tea, forest fruits, special products, farmland irrigation, and animal breeding, in which forest and fruit class heritage site dominate. ②From a regional perspective, the spatial distribution of China’s national agricultural cultural heritage varies greatly, with strong national and regional characteristics. The high-density core area of the national agricultural cultural heritage in 2013 was located in the intersection of Fujian, Zhejiang and Jiangxi. After 2017, the high-density core area moved northward to the Yangtze River Delta region, which was caused by a combination of economic, cultural, and geographical factors. In addition, the agglomeration of the intersection edge area of Guizhou, Hunan and Yunnan provinces has emerged in 2021. In analyzing spatial autocorrelation, drawing on existing relevant research results, the study selected county-level administrative districts as the research unit. The analysis results show that there is a positive spatial correlation between China’s national agricultural cultural heritage sites in 2017 and beyond, with the spatial distribution types mainly being LL and LH. During the study period, the number of LL and HH type areas has been increasing, indicating that the positive spatial correlation between China’s national agricultural cultural heritage sites is gradually strengthening.③In terms of influencing factors, the spatial pattern of China’s national agricultural cultural heritage is affected by factors such as regional economic development level, policy guarantee, transportation accessibility, cultural environment, per capita economic development level, population status, primary industry economic development level, secondary industry economic development level, tourism resource endowment, temperature, precipitation, terrain, and rivers. Among them, the impact of tourism resources, regional economic development level, and policy guarantees are more significant. The explanatory power of the interaction between any two factors is greater than that of a single factor, and there are differences in the strength of the interaction between each influencing factor.